2022
DOI: 10.1017/jog.2022.75
|View full text |Cite
|
Sign up to set email alerts
|

Basal hydrofractures near sticky patches

Abstract: Basal crevasses are macroscopic structural discontinuities at the base of ice sheets and glaciers that arise by fracture. Motivated by observations and by the mechanics of elastic fracture, we hypothesise that spatial variations in basal stress (in the presence of basal water pressure) can promote and localise basal crevassing. We quantify this process in the theoretical context of linear elastic fracture mechanics. We develop a model evaluating the effect of shear-stress variation on the growth of basal creva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 57 publications
2
0
0
Order By: Relevance
“…A similar behavior was observed by Zhang et al. (2023) using LEFM. They observed that for a disturbance on the ground, the ratio between the length of the disturbance and the ice thickness of the glacier L s / H i had an impact on the depth of a basal crevasse.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…A similar behavior was observed by Zhang et al. (2023) using LEFM. They observed that for a disturbance on the ground, the ratio between the length of the disturbance and the ice thickness of the glacier L s / H i had an impact on the depth of a basal crevasse.…”
Section: Resultssupporting
confidence: 89%
“…For a given length of the step, the tensile stress generated by the change at the glacier base propagated less into the ice column for a thicker glacier. A similar behavior was observed by Zhang et al (2023) using LEFM.…”
Section: Dimensional Analysis Of Crevasse Depthsupporting
confidence: 85%